Media optimization for pectinase production from rice bran by solid state bioconversion using Aspergillus niger - Raja Ahmad Izzat Raja Zazali (School of Bioprocess Engineering, University Malaysia Perlis, 2011)
Pectinase is an important hydrolytic enzyme playing a vital role in hydrolyzing pectin molecules that contribute to the degradation of pectin by various mechanisms. Rice bran is an agro-waste from the process of rice milling to produce white rice from brown rice. The microorganism used is Aspergillus niger strain ATCC 16404. The aim of this research is to optimize pectinase production from rice bran based on media composition which is the carbon and nitrogen sources. In addition, it is desired to study the effect of interaction between the parameters, sucrose (1.0-3.0 % w/w) as carbon source and ammonium sulphate (0.3-0.7 % w/w) as nitrogen source. The research was done by using Central Composite Design (CCD) under Response Surface Methodology (RSM). Based on the screening of fermentation period, three days of incubation period was considered as the optimum time for solid state fermentation. In the optimization process, the design contains a total of 11 experimental runs involving replications of central points and organized in a randomized factorial design. From the analysis of variance (ANOVA) using quadratic polynomial equation, maximum pectinase activity of 9.552 U/g was obtained using 2 % (w/w) sucrose and 0.5 % (w/w) ammonium sulphate.